2008
DOI: 10.1016/j.joms.2007.11.032
|View full text |Cite
|
Sign up to set email alerts
|

Zoledronate, Smoking, and Obesity Are Strong Risk Factors for Osteonecrosis of the Jaw: A Case-Control Study

Abstract: Background-Bisphosphonates (BPs) effectively treat metastatic bone disease, hypercalcaemia, and osteoporosis. BP exposure, however, may be associated with osteonecrosis of the jaws (ONJ). The aim of the present study was to estimate the magnitude of the association between intravenous BP exposure and ONJ, and to identify potential confounders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
121
1
12

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(139 citation statements)
references
References 25 publications
4
121
1
12
Order By: Relevance
“…Previous studies have identified steroid usage as a risk factor in BRONJ development (26,29). However, in the present study, steroid usage was not monitored as a risk factor (P=0.8).…”
Section: Discussioncontrasting
confidence: 67%
“…Previous studies have identified steroid usage as a risk factor in BRONJ development (26,29). However, in the present study, steroid usage was not monitored as a risk factor (P=0.8).…”
Section: Discussioncontrasting
confidence: 67%
“…Cases with BRONJ may exhibit osteolytic lesions, sclerosis of cortical bone, reactive changes in the periosteal aspect, sequester formation as well as no radiographic signs. [19][20][21][22][23][24] BRONJ usually occurs more frequently in patients receiving nitrogen-containing bisphosphonates via parenteral route than oral administration. [24][25][26][27] Researchers reported the incidence of BRONJ after oral surgery (like tooth extraction) with cancer patients receiving intravenous bisphosphonates between 6.5% and 51.8%.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21][22][23][24] BRONJ usually occurs more frequently in patients receiving nitrogen-containing bisphosphonates via parenteral route than oral administration. [24][25][26][27] Researchers reported the incidence of BRONJ after oral surgery (like tooth extraction) with cancer patients receiving intravenous bisphosphonates between 6.5% and 51.8%. [28][29][30] Historically, the risk of developing osteonecrosis (at any site) is four times higher in cancer patients than in the normal population and has multiple risk factors, including previous/ concomitant chemotherapy, regular steroid therapy, immunosuppressant therapy, radiation therapy, diabetes, hypertension, obesity, certain gene mutations, tobacco habit, alcoholism 19,[24][25][26][27] as well as poor oral hygiene, chronic oral trauma, previously existing local infection and a history of dental procedures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bifosfonat kullanımına bağlı gelişen kemik nekrozları intravenöz yolla kullanımda, oral yolla kullanımdan daha büyük bir risk oluştursa da, oral kullanım sonrasında da gelişen osteonekroz vakaları mevcuttur. [13][14][15] Bifosfonatların neden özellikle mandibula ve maksillada osteonekroz oluşturduğu kesin olarak açıklanamamıştır. Bifosfonatlar yenilenme oranı yüksek olan kemiklerde ve komşu yumuşak dokularda yüksek oranda biri- kirler.…”
unclassified